Long-term evaluation of factors affecting removal torque of microimplants - Ho-Jin Kim (SpringerOpen, 2021)
Abstract Background The current study aimed to evaluate factors affecting the long-term stability of microimplants using removal torque and the correlation between removal torque and clinical variables. Materials and methods This research evaluated 703 microimplants placed in 354 patients (mean age: 30.4 ± 12.1 years). The removal torque was evaluated according to various clinical variables including sex, age, placement site, microimplant size, and placement method (self-drilling versus pre-drilling). Pearson correlation and stepwise multiple linear regression analyses were performed to investigate different variables and their association with removal torque. Results The mean removal torque was significantly higher in the mandible (4.46 N cm) than in the maxilla (3.73 N cm). The values in the posterior teeth/retromolar areas were significantly higher than those in the anterior teeth area. There were no significant difference in terms of sex. Teenagers had a lower removal torque than older adults in the mandible, but not in the maxilla. Microimplants with a greater length and diameter, except for those with a greater diameter in the maxilla, was associated with a higher removal torque. Regardless of placement torque, the removal torque convergently reached approximately 4 N cm in both placement methods. The removal torque was significantly correlated with screw length in the self-drilling group and with diameter in the pre-drilling group. Conclusions Removal torque was related with placement site, age, placement method, and length and diameter of microimplants.